2005
DOI: 10.1111/j.1365-2699.2005.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Lentic odonates have larger and more northern ranges than lotic species

Abstract: Aim  We analysed latitudinal range, centres of distribution and northern range boundaries of dragonflies and damselflies occurring in Europe and North America with respect to larval habitat (standing water = lentic and running water = lotic). As lentic water bodies are thought to be less predictable in space and time than lotic habitats, species adapted to standing waters depend on effective dispersal ability for long‐term survival. If species occurring in lentic habitats have a higher propensity for dispersal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
125
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 49 publications
9
125
2
1
Order By: Relevance
“…This is underlined by the tendency towards stronger over-prediction of lotic species ranges when comparing projected and observed ranges for 2006. Both findings support the HSDH, suggesting that lower habitat stability selects for stronger dispersal abilities [3,4] (see the electronic supplementary material, discussion for details on the effects of range size, phylogeny, threshold technique and on other deviances from the overall pattern). The observed differences in range filling could be confounded by habitat availability, e.g.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is underlined by the tendency towards stronger over-prediction of lotic species ranges when comparing projected and observed ranges for 2006. Both findings support the HSDH, suggesting that lower habitat stability selects for stronger dispersal abilities [3,4] (see the electronic supplementary material, discussion for details on the effects of range size, phylogeny, threshold technique and on other deviances from the overall pattern). The observed differences in range filling could be confounded by habitat availability, e.g.…”
Section: Discussionsupporting
confidence: 57%
“…Specifically, we hypothesize that if their habitats are more likely to disappear within shorter periods of time, lentic species should have evolved a higher propensity for dispersal than lotic species [3]. Support for this hypothesis-hereafter referred to as the habitat -stability -dispersal hypothesis (HSDH)-comes from several studies, which showed that lentic species have larger range sizes [4] and a lower genetic diversity among populations [5,6] than lotic species. Furthermore, post-glacial re-colonization of northern Europe was probably faster for lentic than for lotic species [7][8][9].…”
Section: Introductionmentioning
confidence: 97%
“…Generally, water velocity, temperature, shading, disturbance, type of substrate, trophy, aquatic vegetation (its spatial structure and abundance) and predation risk are considered to be the most important factors shaping assemblages of Odonata larvae (Buchwald, 1992;Buss et al, 2004;Johansson et al, 2006;McCauley, 2007;Strange et al, 2007;Buczyński, 2015). The regional distribution of Odonata seems to be mostly affected by dispersal at the adult stage (Hof et al, 2006) while the local distribution is probably mainly affected by interactions at the larva stage (McCauley, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, these species could only achieve wide distribution through active (e.g., aerial flight of merolimnic insects) and passive (e.g., by wind, animal vectors) dispersal over inhospitable habitats (Bilton et al, 2001 and references therein). Recently, species ranges of European aquatic beetles (Ribera and Vogler, 2000;Ribera et al, 2003) and European and North-American dragonflies (Hof et al, 2006) were conclusively correlated to dispersal propensity of these organisms, which in turn depends on their habitat preferences. Hof et al (2006) also showed that the current distribution of dragonflies in Europe and North America is determined by an interplay of the species' dispersal propensity and the geographical orientation of mountain ranges.…”
Section: Introductionmentioning
confidence: 99%
“…The most important among them are species' ecological requirements and dispersal abilities (Gaston, 1994;Ribera and Vogler, 2000;Hof et al, 2006), geographical barriers (Adams and Woodward, 1989;Bernatchez and Wilson, 1998), and evolutionary, geological, and climatic historical processes (Webb and Bartlein, 1992;Dynesius and Jansson, 2000). A complex interplay of these factors, but not any single factor, is currently thought to shape the geographical ranges of species (Lomolino et al, 2006;Whittaker et al, 2007;Hof et al, 2008;Bonada et al, 2009, and the references above).…”
Section: Introductionmentioning
confidence: 99%